Use of Additives and Physical Methods to Maintain the Quality of Fresh Cut Produces - Silveira, Ana Cecilia (Agrociencia Uruguay, 2017)
Fresh cut or minimally processed products are those subjected to different unitary operations, such as peeling, cutting, washing, and disinfection, among others, that modify their appearance but keep their tissues alive. The maintenance of the nutritional and functional organoleptic quality of minimally processed products makes it necessary to reduce deterioration processes such as enzymatic browning and softening. These processes are controlled with chemical additives. In the case of enzymatic browning, acidulants and chelating agents, among others, are used, while calcium salts are used for firmness maintenance. However, the current trend of reducing the use of chemical additives generates the need to develop alternative methods for deterioration processes control, with emphasis on physical methods, including heat treatments and ionizing and non-ionizing radiation (UV-C, microwave, ultrasound). On the other hand, both chemical and physical methods by themselves have a limited activity. Their combination determines synergistic effects (obstacle technologies) that lead to greater preservation of quality. This work addresses the use of chemical additives and physical treatments, both alone and in combination, to control softening and enzymatic browning in minimally processed products.